2016
DOI: 10.1097/hjh.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

The association between blood pressure and lipid levels in Europe

Abstract: Small but statistically significant associations between lipid levels and BP were observed in a large, multinational European population. Further research is warranted to assess the causality of this association and its implications on the management of patients with both hypertension and dyslipidaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…In hypertensive patients, SBP had statistically significant correlation with serum LDL-C and TG levels which tended to rise as the duration of hypertension advances. Plethora of studies such as a study conducted in Europe, 55 another study carried out in India, 12 in Nigeria, 27 and a study conducted in Ethiopia 24 are in trajectory with this study. Hypertension and lipid abnormalities are well known to frequently coexist and synergize to be risk factors for CVD.…”
Section: Discussionmentioning
confidence: 76%
“…In hypertensive patients, SBP had statistically significant correlation with serum LDL-C and TG levels which tended to rise as the duration of hypertension advances. Plethora of studies such as a study conducted in Europe, 55 another study carried out in India, 12 in Nigeria, 27 and a study conducted in Ethiopia 24 are in trajectory with this study. Hypertension and lipid abnormalities are well known to frequently coexist and synergize to be risk factors for CVD.…”
Section: Discussionmentioning
confidence: 76%
“…Based on the evidence, we evaluated BMI [ 4 ], smoking status (non-smoker, ex-smoker, current smoker) [ 4 , 10 ], renal function [ 15 ], LDL-c [ 16 ], parental HTN (yes/no) [ 4 , 5 ], and diabetes at baseline (yes/no) [ 17 ] as potential risk factors. BMI was classified into two groups (<23 and ≥23 kg/m 2 ) and reduced renal function was defined as an estimated glomerular filtration rate (eGFR) < 60 mL/min per 1.73 m 2 [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Dyslipidemia are recognized as a strong predictor of cardiovascular disease and several studies have suggested a positive correlation between dyslipidemia and hypertension [ 10 , 11 ]. Leptin, an adipocytokine produced by adipose tissue, is associated with dyslipidemia [ 12 ], and recent study has demonstrated that leptin contributes to hypertension through upregulation of central renin–angiotensin system and proinflammatory cytokines [ 13 ].…”
Section: Introductionmentioning
confidence: 99%